Inteligência em portadores de neurofibromatose 1 - Bolini, Helenice Bianchi (2010)
The practical problem observed referred to the clinical symptoms of NF1, involving intellectual performance and psychosocial characteristics of their carriers. This sends us to the NF1-intelligence interface. Objective: To identify and compare indices of intelligence and their frequencies in patients with NF1, attended at CEPAN. Methods and Casuistry: Medical records were used in research, semi-structured interview, the Wechsler Scales and Test Progressive Matrices Scale-General. Were applied indidually, to the 77 subjects, of which 30 patients with NF1, 17 family members, and 30 non- carriers between 2006 and 2010. The data were treated qualitative-quantitative. Results: The socioeconomic and cultural rights did not differ between subjects. Minors (<20 ) and larger (>20 ) time spent in the execution of Test Progressive Matrices Sacale-General were relatives of patients with NF1 and most were using medication. Mean correct responses were lower in patients with NF1, they had one and two symptoms that bothered when they were diagnosed, currently, the troubled portability three, four and two symptoms. Patients with NF1 had their first symptoms identified with more than five years age, they had relatives suffering from NF1 1st and/or 2nd degrees of relatedness (vertical transmission). They had mild MR and moderate, and learning disabilities. The subjects of this investigation showed TIQ; VIQ; TIQ/Gc; IOP/Gv; IVP/Gt average and below average; although the ability Reasoning/ Fluid Intelligence Gf category V. Conclusions: The subjects of this investigation have average and average lower, with limited sustainability. There are differences in intellectual performance among them: relatives of patients with NF1 are superior to the carriers and no- carriers are superior to both. There are mental retardation, learning disabilities, difficulties visual-perceptual-motor, memory impairments, and speech in written and spoken language in patients with NF1. There are no correlations between TIQ/Gc; IMO/Gsm; ICV/Gc; IOP/Gv; IVP/Gt and number of symptoms. There is no correlation between IQ, intellectual level, types, numbers, uncomfortable symptoms and age of onset of symptoms.